SCIENTIFIC-BASED NUMERACY LITERACY TEACHING MATERIALS IN LEARNING MANAGEMENT: STUDENT MOTIVATION AND HIGHER THINKING SKILLS - Lisnasari, Srie Faizah; Jainab, Jainab; Syafnan, Syafnan (Universitas Labuhanbatu, 2025)
Purpose – This study aims to analyse the effect of science-based numeracy literacy teaching materials in learning management on students' motivation and higher order thinking skills.Methodology – This study uses a quantitative approach with a quasi-experimental method that applies a nonequivalent control group design. In this study, the sample was selected using a purposive sampling technique, so that the subjects taken have met certain criteria that are in accordance with the objectives of the study. The instruments used in data collection include questionnaires to measure motivation and tests designed to assess high order thinking skills. The data obtained were analyzed using an independent sample t-test, which aims to see significant differences between the experimental group and the control group in the variables studied.Findings – The results showed a difference in the average score of the experimental class posttest motivation of 80.77, while the control group posttest was 70.77, while the average score of higher order thinking skills of the experimental class posttest was 80.36, while the control group posttest was 65.06. Sig (2-tailed) independent sample t-test value of motivation and higher order thinking skills is 0.000 <0.05. This shows that there is a significant difference (real) between the average score of motivation and higher order thinking skills of experimental and control group students by using scientific-based numeracy literacy teaching materials in learning management.Contribution – This research makes a significant contribution to the development of scientific-based numeracy literacy teaching materials, especially in the context of learning management in higher education. With the existence of teaching materials that are systematically designed and scientifically based, this research plays a role in improving the quality of learning, especially in optimising the interaction between lecturers and students.